Neural Networks for Implicit Representations of 3D Scenes - Schirmer, Luiz; Schardong, Guilherme; Silva, Vinícius da; Lopes, Hélio; Novello, Tiago; Yukimura, Daniel; Magalhaes, Thales; Paz, Hallison; Velho, Luiz (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2021)
This survey presents methods that use neural networks for implicit representations of 3D geometry — neural implicit functions. We explore the different aspects of neural implicit functions for shape modeling and synthesis. We aim to provide a theoretical analysis of 3D shape reconstruction using deep neural networks and introduce a discussion between researchers interested in this research field.